Systematics, biogeography, and diversification of Scytalopus tapaculos (Rhinocryptidae), an enigmatic radiation of Neotropical montane birds. (21st March 2020) - Cadena, Carlos Daniel; Cuervo, Andrés M; Céspedes, Laura N; Bravo, Gustavo A; Krabbe, Niels; Schulenberg, Thomas S; Derryberry, Graham E; Silveira, Luis Fabio; Derryberry, Elizabeth P; Brumfield, Robb T; Fjeldså, Jon
Abstract: We studied the phylogeny, biogeography, and diversification of suboscine passerines in the genus Scytalopus (Rhinocryptidae), a widespread, species-rich, and taxonomically challenging group of Neotropical birds. We analyzed nuclear (exons, regions flanking ultraconserved elements) and mitochondrial (ND2) DNA sequence data for a taxonomically and geographically comprehensive sample of specimens collected from Costa Rica to Patagonia and Brazil. We found that Scytalopus is a monophyletic group sister to Eugralla and consists of 3 main clades roughly distributed in (1) the Southern Andes, (2) eastern Brazil, and (3) the Tropical Andes and Central America. The clades from the Southern Andes and eastern Brazil are sister to each other. Despite their confusing uniformity in plumage coloration, body shape, and overall appearance, rates of species accumulation through time in Scytalopus since the origin of the clade in the Late Miocene are unusually high compared with those of other birds, suggesting rapid non-adaptive diversification in the group. We attribute this to their limited dispersal abilities making them speciation-prone and their occurrence in a complex landscape with numerous barriers promoting allopatric differentiation. Divergence times among species and downturns in species accumulation rates in recent times suggest that most speciation events in Scytalopus predate climatic oscillations of the Pleistocene. Our analyses identified various cases of strong genetic structure within species and lack of monophyly of taxa, flagging populations which likely merit additional study to clarify their taxonomic status. In particular, detailed analyses of species limits are due in S. parvirostris, S. latrans, S. speluncae, the S. atratus complex, and the Southern Andes clade.